Esélyegyenlőség és diszkrimináció - fogyatékos és megváltozott munkaképességű személyek a munka világában - Dajnoki, Krisztina (Közép-Európai Közlemények, 2012)
All the people should get different, but equal chances to live his privately chosen life meaningfully. Generally existing negative beliefs, prejudices and the discriminate behaviour originated from them also valid for the world of labour, and as a result, an invalid picture develops about the disabled and handicapped people among employers. Considering human resource management equality means that all employees could have the same job possibilities, and their performance and results to be judged in the same way in the aspect of their capabilities. The raised rehabilitation funding from the 1st January, 2010 means a growing number of organisations want to employ disabled people, but in the meantime the employment of these people faces several challenges because of the insufficient information. Our research so called “Equality Human Research Management” aims to reveal the tasks, nature, processes and methods of employing and managing handicapped and changed capability employees. To successfully (re)integrate the disabled and handicapped people, we must be aware of and must consider the chances, the nature of the affected and also the expectations of the employer so that the disabled get really equal opportunities in the workplace.